2020
DOI: 10.1002/ldr.3779
|View full text |Cite
|
Sign up to set email alerts
|

Factors governing soil water repellency under tillage management: The role of pore structure and hydrophobic substances

Abstract: Soil water repellency (SWR) has significant effects on soil degradation by changing some soil processes (e.g., carbon sequestration and soil erosion). Understanding the influence factors of SWR under conservation agriculture are playing a vital role in the sustainable development for improving soil quality. However, how soil pore structure influence on SWR remains unclear. We aim to assess the impact of hydrophobic substances and pore structure on SWR. Here we conducted two long‐term experimental fields with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 86 publications
(156 reference statements)
0
22
0
Order By: Relevance
“…For soil S2, we observed a gradual growing tendency with the remediation time, where it increased over 3 times for S2D (18 years of remediation) in comparison to S2A (1 year of remediation). It is considered that higher hydrophobicity improves the long-lasting aggregate stability of SOM [24,25]. Moreover, this increase in hydrophobicity in remediated soils may strongly affect the water availability to plants and also increase the surface runoff and thus increase the susceptibility of the soil to secondary erosion [26].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For soil S2, we observed a gradual growing tendency with the remediation time, where it increased over 3 times for S2D (18 years of remediation) in comparison to S2A (1 year of remediation). It is considered that higher hydrophobicity improves the long-lasting aggregate stability of SOM [24,25]. Moreover, this increase in hydrophobicity in remediated soils may strongly affect the water availability to plants and also increase the surface runoff and thus increase the susceptibility of the soil to secondary erosion [26].…”
Section: Resultsmentioning
confidence: 99%
“…For soil S2, we observed a gradual growing tendency with the remediation time, where it increased over 3 times for S2D (18 years of remediation) in comparison to S2A (1 year of remediation). It is considered that higher hydrophobicity improves the long-lasting aggregate stability of SOM [24,25]. Aromatic structures are considered to be difficult for decomposition, and they also have a long half-life in soil.…”
Section: Resultsmentioning
confidence: 99%
“…This was likely because no-tillage creates heterogeneous soil (Sun et al, 2018). Our previous study in this experiment site showed that soil depth had a significant influence on soil moisture, bulk density, porosity, and aggregate stability in 0-20 cm soil depth (Li et al, 2020a), which could lead that microbial properties are different with changing in topsoil depth. In addition, some previous studies also showed the difference in enzyme activities and microbial properties under different topsoil depths (Fierer et al, 2003;Mathew et al, 2012).…”
Section: Pls-pm Analysismentioning
confidence: 86%
“…The main reason is that nitrate nitrogen can transport with soil water movement, resulting in nitrogen leached into deeper soil depth . In addition, our previous study showed that NT increased the soil porosity of >55 μm diameter pores compared to the CT treatment, which indicated that NT could increase soil water infiltration and nitrogen leaching (Li, et al, 2020a).…”
Section: Relationship Of Soil Microbial Characteristic and Microbial Cuementioning
confidence: 89%
“…Therefore, management practices that increase C inputs, such as straw incorporation, which is known to restore SOC content, are applied as integrated approaches. The optimization of tillage management with the return of straw is being promoted for ameliorating soil conditions, which will facilitate soil quality and sustainable crop productivity [5][6][7][8][9][10][11][12]. Moreover, it is of great significance to clarify the response characteristics of soil quality to different tillage methods.…”
Section: Introductionmentioning
confidence: 99%